2016
DOI: 10.1177/1527002516673407
|View full text |Cite
|
Sign up to set email alerts
|

The Game Is Good at the Top

Abstract: Collegiate football may provide advertising for universities, attracting larger pools of applicants and leading to more academically qualified student bodies. Football may also build school spirit, reducing attrition and improving long-run graduation rates. This analysis uses data from 2001 to 2004 for available National Collegiate Athletic Association Division-1 institutions to examine the advertising and effectiveness effects of football. Using both general linear model and linear-in-means model estimation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Given the vast differences in these universities, it seems likely that both the advertising and effectiveness effects of intercollegiate athletics may be significantly different between D-I and D-III. In essence, these distinctions are similar to those between NCAA FBS and FCS among D-I institutions as discussed in Segura and Willner (2018).…”
Section: Literaturementioning
confidence: 62%
See 1 more Smart Citation
“…Given the vast differences in these universities, it seems likely that both the advertising and effectiveness effects of intercollegiate athletics may be significantly different between D-I and D-III. In essence, these distinctions are similar to those between NCAA FBS and FCS among D-I institutions as discussed in Segura and Willner (2018).…”
Section: Literaturementioning
confidence: 62%
“…Yet the advertising effect may have consequences for effectiveness of university athletics. Segura and Willner (2018) use a linear-in-means approach with D-I universities to account for this potential endogeneity. They find that, for football, both advertising and effectiveness are positive and that bowl appearances are successful as advertising.…”
Section: Literaturementioning
confidence: 99%
“…Then focusing on SAT test scores, Pope and Pope (2008) also found the increase in applications was comprised of both low and high scoring applicants, thereby allowing schools to be more selective in the makeup of incoming freshman class. Lastly, Segura and Willner (2016) used football Bowl Game invitations to examine their impact on university academics and found that Bowl Game invitations served to increase the median SAT scores at several universities.…”
Section: Section 1: Literature Reviewmentioning
confidence: 99%
“…While SAT scores received most of the attention, research also examined other studentrelated academic outcomes and athletic success. Tucker (1992) and Segura and Willner (2016) find evidence that graduation rates decreased with athletic success or were unrelated to athletic success. Rishe 2003 Another line of research examines the relationship between the number of undergraduate applicants to a school and athletic success.…”
Section: Intercollegiate Athletics and Student Outcomesmentioning
confidence: 99%
“…Early studies generally found only football success related to higher SAT scores while later studies found only basketball success related to higher scores. Only Tucker and Amato (2006), Pope (2009), Smith (2008), and Segura and Willner (2016) use panel data that allow for fixed effects to control for unobservable institution-level heterogeneity.…”
Section: Intercollegiate Athletics and Student Outcomesmentioning
confidence: 99%